OpenStudy (anonymous):

solve the system x=3y+9 and 9-x=-3y

3 years ago
OpenStudy (anonymous):

hi welcome to openstudy!! do you know how to apply substitution method?

3 years ago
OpenStudy (anonymous):

since equation is already arranged in terms of x,, substitute this equation into the second equation. it will look like this: x=3y+9 ->eqn 1 9-x=-3y ->eqn 2 sub eqn 1 to eqn 2: 9- (3y+9)=-3y now can you simplify this new equation and solve for y?

3 years ago
OpenStudy (anonymous):

@Annie17 still there?

3 years ago
OpenStudy (anonymous):

Yes I am. And I can simplify it now. Thank you. :)

3 years ago
Similar Questions: